Relaxed territoriality amid female trickery in a solitary carnivore. (December 2022) - le Roex, Nikki; Mann, Gareth K.H.; Hunter, Luke T.B.; Balme, Guy A.
Abstract : Territoriality (the defence of exclusive home ranges) is a strategy utilized within mammal populations to maximize individual fitness by monopolizing available resources. There is a trade-off, however, between acquiring the resources necessary for survival and reproduction and the cost of defending their exclusive use. Clarifying the sociospatial organization of wildlife populations is vital for understanding intraspecific competition and reproductive behaviour and, ultimately, conserving vulnerable or endangered species. We evaluated territorial behaviour in a solitary carnivore, the African leopard, Panthera pardus, under high-density conditions. We also assessed the influence of resource availability, sex-specific mating tactics and kinship on space sharing within the observed sociospatial structure. Both male and female leopards exhibited relaxed territoriality, with considerable intrasexual overlap occurring among both sexes, indicative of a risk aversion strategy. The risk of serious injury or death due to frequent territorial altercations in such a high-density system negated the benefits of strict spatial boundaries. Space sharing occurred more frequently in resource-rich areas: males overlapped more commonly in areas with high female density, and males and females overlapped more commonly in areas of high prey density. Males competed for access to females rather than monopoly of their home ranges; we hypothesize that the extralimital mating excursions undertaken by female leopards probably reduce the benefit of female monopoly (and consequently, of female defence) in this polygamous species. Space sharing among females was primarily driven by kinship; related females exhibited greater overlap than unrelated females, suggesting kinship benefits to space sharing among mother–daughter pairs. The contributions of resource availability, sex-specific mating tactics and kinship towards creating conditions permitting relaxed territoriality illustrate the complexity of ecological, demographic and behavioural factors involved in the sociospatial organization of solitary carnivores. Highlights: Male and female leopards display relaxed territoriality indicative of risk aversion. Considerable intrasexual overlap occurred among male and female leopards. For males, space sharing occurred more often in areas with high female density. Males competed for access to females rather than monopoly of their home ranges. Space sharing among females was primarily driven by kinship.